Brucellosis Control in Malta and Serbia: A One Health Evaluation - Buttigieg, Sandra C.; Savic, Sara; Cauchi, Daniel; Lautier, Elaine; Canali, Massimo; Aragrande, Maurizio (Frontiers in Veterinary Science, 2018)
Brucellosis, also known as “undulant fever” or “Malta fever” is a zoonotic infection caused by microorganisms belonging to Brucella, a genus of gram-negative coccobacilli that behave as facultative intracellular pathogens of ruminants, swine and other animals. Brucellosis is a threat to public health, hence identifying the optimal way of preventing disease spread is important. Under certain circumstances, integrated, multidisciplinary ‘One Health’ (OH) initiatives provide added value compared to unidisciplinary or conventional health initiatives. Conceptualising and conducting evaluations of OH approaches may help facilitate decisions on resource allocation. This article historically describes and compares Malta’s 1995-1997 with Serbia’s 2004-2006 brucellosis control programmes and quantitatively assesses the extent to which they were compliant with a OH approach. For both case studies, we describe the OH initiative and the system within which it operates. Characteristic OH operations (i.e. thinking, planning, working) and supporting infrastructures (to allow sharing, learning and systemic organization) were evaluated. We scored the different aspects of these programmes, with values ranging from zero to one (1 = strong integration of OH). Malta demonstrated a higher OH index (0.54) and ratio (1.37) than Serbia (0.49 and 1.14 respectively). We conclude that context and timing are key to determining how, when and why a One Health approach should be applied. The adoption of a true OH approach that involved systemic organization, leadership clarity and transdisciplinary communication, collaboration, and co-ordination was essential to Malta’s successful eradication of brucellosis after several failed attempts. In contrast, contextual factors in Serbia permitted the successful adoption of a primarily sectorial approach for short term control of brucellosis. However, while a fully-fledged transdisciplinary OH approach was not initially required, it is likely to be key to maintenance of brucellosis control in the medium and long term. Through these two case studies, we demonstrate that One Health initiatives should be applied at the right place, at the right time, with the right people and using the appropriate conditions/infrastructure. Lastly, OH evaluations should include economic assessments to identify optimal of resources in these situations, thereby justifying funding and political support required.